2012
DOI: 10.1139/x2012-008
|View full text |Cite
|
Sign up to set email alerts
|

Consistent negative temperature sensitivity and positive influence of precipitation on growth of floodplain Picea glauca in Interior Alaska

Abstract: This paper calibrates climate controls over radial growth of floodplain white spruce ( Picea glauca (Moench) Voss) and examines whether growth in these populations responds similarly to climate as upland trees in Interior Alaska. Floodplain white spruce trees hold previously unrecognized potential for long-term climate reconstruction because they are the source of driftwood that becomes frozen in coastal deposits, where archeological timbers and beach logs represent well-preserved datable material. We compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 26 publications
3
32
0
Order By: Relevance
“…Although numerous studies regarding the drought tolerance and resilience of forest trees in relation to their site conditions exist [29,31,37,[70][71][72], the behavior of urban trees to drought is rarely researched [33,38,39]. However, urban trees are of great benefit to the climate of a city and the well-being of its citizens.…”
Section: Tree Ring Analysis: Quantification Of Growth Of Urban Trees mentioning
confidence: 99%
“…Although numerous studies regarding the drought tolerance and resilience of forest trees in relation to their site conditions exist [29,31,37,[70][71][72], the behavior of urban trees to drought is rarely researched [33,38,39]. However, urban trees are of great benefit to the climate of a city and the well-being of its citizens.…”
Section: Tree Ring Analysis: Quantification Of Growth Of Urban Trees mentioning
confidence: 99%
“…However, there are also numerous studies that have found no evidence for a recent decoupling of the temperatureegrowth relationship (e.g. Juday and Alix, 2012;Weijers et al 2012;Young et al 2012). In other words, the DP is neither ubiquitous nor uni-directional.…”
Section: Introductionmentioning
confidence: 98%
“…These "negative" trends were linked, among other factors, to heat and hydric stresses resulting from rising temperatures and more frequent, longer-lasting, and harsher drought episodes (Barber, Juday, & Finney, 2000;Girardin et al, 2016;Juday & Alix, 2012;Nicklen et al, 2018;Trugman, Medvigy, Anderegg, & Pacala, 2018;Zhang et al, 2008). In contrast, other studies provided strong evidence for increased growth rates and higher stand productivity (Beck et al, 2011;Girardin et al, 2011;Hember, Kurz, & Coops, 2017).…”
Section: Introductionmentioning
confidence: 99%